Responses of early-successional songbirds to a two-stage shelterwood harvest for oak forest regeneration - Eric L. Margenau; Yong Wang; Callie J. Schweitzer; Brandie K. Stringer (Avian Research, 2018)
Abstract Background The early stage of forest succession following disturbance is characterized by a shift in songbird composition as well as increased avian richness due to increased herbaceous growth in the forest understory. However, regeneration of woody species eventually outcompetes the herbaceous understory, subsequently shifting vegetation communities and decreasing availability of vital foraging and nesting cover for disturbance-dependent birds, ultimately resulting in their displacement. These early stages following forest disturbance, which are declining throughout the eastern United States, are ephemeral in nature and birds depend on such disturbances for nesting and other purposes throughout their lives. Methods We investigated the use of a two-stage shelterwood method to manage long-term persistence of seven early successional songbirds over a 13-year period in an upland hardwood forest within the southern end of the mid-Cumberland Plateau in the eastern United States. Results Canopy and midstory gaps created after initial harvest were quickly exploited by tree growth and canopy cover returned to these areas, accelerating the displacement of early-successional species. Woody stem densities increased substantially following stage two harvest as advanced tree regeneration combined with the re-opening of the overstory layer increased resource competition for early-successional plants in the understory. Carolina Wren (Thryothorus ludovicianus), Eastern Towhee (Pipilo erythrophthalmus), Indigo Bunting (Passerina cyanea), and Yellow-breasted Chat (Icteria virens) were characterized by immediate increases following initial harvest in 2001; while the American Goldfinch (Spinus tristis), Prairie Warbler (Setophaga discolor), and White-eyed Vireo (Vireo griseus) did not show an immediate response. Stage two harvest in 2011 rejuvenated vegetation which benefitted focal species, with six of seven species showing increases in densities between 2010 and 2012. Conclusion The two-stage shelterwood method created conditions advantageous to early-successional birds by helping to re-establish understory vegetation through periodic disturbance to the canopy layer. This method provides evidence that early-successional species can be managed long-term (> 15 years) while using relatively small spatial disturbance through the two-stage shelterwood method.